2019
DOI: 10.1002/hyp.13557
|View full text |Cite
|
Sign up to set email alerts
|

Ice cover exists: A quick method to delineate groundwater inputs in running waters for cold and temperate regions

Abstract: Groundwater can be important in regulating stream thermal regimes in cold, temperate regions, and as such, it can be a significant factor for aquatic biota habits and habitats. Groundwater typically remains at a constant temperature through time; that is, it is warmer than surface water in winter and cooler in summer. Further, small tributaries are often dominated by groundwater during low flows of winter and summer.We exploit these thermal patterns to identify and delineate tributary/groundwater inputs along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…There was no deviation of anomaly locations between 2008, 2009, and the field observations of 2010 (Wilbur, ). This is consistent with other studies that found thermal anomalies in the Cains River were spatially and temporally stable between 2008/2009 and 2014 (see O'Sullivan, Linnansaari, & Curry, ). The river's groundwater inputs are derived from intermediate to long, groundwater flow paths, are less susceptible to fluxes in contemporaneous climate, and therefore are spatially and temporally stable.…”
Section: Methodssupporting
confidence: 92%
“…There was no deviation of anomaly locations between 2008, 2009, and the field observations of 2010 (Wilbur, ). This is consistent with other studies that found thermal anomalies in the Cains River were spatially and temporally stable between 2008/2009 and 2014 (see O'Sullivan, Linnansaari, & Curry, ). The river's groundwater inputs are derived from intermediate to long, groundwater flow paths, are less susceptible to fluxes in contemporaneous climate, and therefore are spatially and temporally stable.…”
Section: Methodssupporting
confidence: 92%
“…In this study, we found mixed success and sometimes poor outcomes for the SSN models, and the reason appears to be a function of geology. Emerging from our current and past studies (Monk et al, 2013; O'Sullivan, Linnansaari, et al, 2019) and relatively poor SSN performance in regions with similarly variable geology and topography (e.g., Detenbeck et al, 2016—New England, northeastern United States) is a working hypothesis that SSNs are effective in regions where the relationship between climate, groundwater, and topography is regionally constant, that is, unidirectional or bidirectional (Gleeson & Manning, 2008; Tóth, 1962).…”
Section: Discussionmentioning
confidence: 85%
“…The influence of geology on river flow and temperature at the catchment‐scale has been largely neglected in process and modeling studies, but geology is emerging as a key hydrological control (e.g., Briggs et al, 2017; Carlier et al, 2019; O'Sullivan, Linnansaari, et al, 2019; Tague & Grant, 2004). Current SSN models have great potential, but their applicability for hydrological process analysis is likely limited to areas with constant groundwater/topography regimes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a well-established supervised maximum likelihood classification (sMLC) machine learning algorithm to classify the objects in the sonar images described above. sMLC is based on Bayesian probability theory [37] and requires an initial training data suite to define the classes of interest. In this study, those classes were (1) potential Shortnose Sturgeon, and (2) river bed.…”
Section: Image Classificationmentioning
confidence: 99%